personal styles and their Relationship with types of leadership for hospital, directors (field study in Oum El Bouaghi and Constantine city) - khara, djihad (Milev Journal of Research and Studies, 2016)
The director of the hospital as a link between its members and plans and objectives, so for the development prosperity of the organization to be director of a personality pattern can repeat the conduct of the organization for the better and uses a style of leadership helps employees to provide the best .Stan designed to detect the most prominent patterns and types of personal leadership and find a correlation between them. We used the descriptive approach correlative on a sample (30)director of the state Oum El Bouaghi and constantine , we used two measures . We concluded that most prominent personal styles are style" C", then style "B" ,then style" A" ,and the most prominent types of leadership are type autocratic, Type democratic, types free, and find a correlation between personal leadership styles and types of the hospital directors.